Clergy involvement in occupational safety and health - Finn, Peter (Journal of religion and health, 1981)
The toll exacted by occupational injuries and illnesses on employed people involves a degree of personal and family suffering of such magnitude that clergy can legitimately consider it a part of their pastoral responsibilities to address the problem. Several cogent reasons for clergy involvement in occupational safety and health are provided, along with approaches clergy can implement to help parishioners reduce their workplace risks. Resources for assistance in engaging in these activities are suggested.